Properties of condensed bacteriophage T4 DNA isolated from Escherichia coli infected with bacteriophage T4. - Hamilton, S (1976)
Methods developed for isolating bacterial nucleoids were applied to bacteria infected with phage T4. The replicating pool of T4 DNA was isolated as a particle composed of condensed T4 DNA and certain RNA and protein components of the cell. The particles have a narrow sedimentation profile (weight-average s=2,500S) and have, on average, a T4 DNA content similar to that of the infected cell. Their dimensions observed via electron and fluorescence microscopy are similar to the dimensions of the intracellular DNA pool. The DNA packaging density is less than that of the isolated bacterial nucleoid but appears to be roughly similar to its state in vivo. Host-cell proteins and T4-specific proteins bound to the DNA were characterized by electrophoresis on polyacrylamide gels. The major host proteins are the RNA polymerase subunits and two envelope proteins (molecular weights, 36,000 and 31,000). Other major proteins of the host cell were absent or barely detectable. Single-strand breaks can be introduced into the DNA with gamma radiation or DNase without affecting its sedimentation rate. This and other studies of the effects of intercalated ethidium molecules have suggested that the average superhelical density of the condensed DNA is small. However, these studies also indicated that there may be a few domains in the DNA that become positively supercoiled in the presence of high concentrations of ethidium bromide. In contrast to the Escherichia coli nucleoid, the T4 DNA structure remains condensed after the RNA and protein components have been removed (although there may be slight relaxation in the state of condensation under these conditions).